Anti-scorching EPDM (ethylene-propylene-diene monomer) material with good fluidity and preparation method thereof

By introducing modified phenolic resin and composite silica aerogel into EPDM materials, the problem of poor anti-coke performance of existing EPDM materials is solved, and the effect of good fluidity and high heat resistance is achieved, reducing environmental pollution.

CN119798872APending Publication Date: 2025-04-11DONGGUAN LIQUN RONGXING POLYMER TECH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411998218.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The anti-coking performance of existing EPDM materials is poor, resulting in premature vulcanization during processing, deterioration of fluidity, affecting production efficiency, and scorching will increase viscosity, increase processing difficulty, and release harmful gases during scorching, polluting the environment and the human body.

Method used

By introducing components such as modified phenolic resin and composite silica aerogel, an EPDM material with good anti-calorie fluidity is prepared. Modified phenolic resins restrict the movement of EPDM molecular chains and delay the occurrence of scorching through uniform dispersion; composite silica aerogels have the characteristics of multi-porous and high specific surface area, which play a role in reinforcing and thermal conductivity, and jointly improve the heat resistance of EPDM materials.

Benefits of technology

It significantly improves the anti-coke performance and fluidity of EPDM materials, extends the scorching time, improves the processing performance, and improves the heat-resistant aging performance of the material, reduces the release of harmful gases, and protects the environment and human health.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005225385070000081
    Figure BDA0005225385070000081
  • Figure BDA0005225385070000091
    Figure BDA0005225385070000091
Patent Text Reader

Abstract

The invention relates to the technical field of production of rubber materials, in particular to an anti-scorching EPDM (Ethylene-Propylene-Diene Monomer) material with good fluidity and a preparation method thereof. The EPDM material is prepared from the following raw materials in parts by weight: 50 to 80 parts of EPDM raw rubber, 5 to 8 parts of phenolic resin, 0.2 to 3 parts of scorch retarder, 4 to 7 parts of zinc methacrylate, 0.5 to 3 parts of stearic acid, 5 to 15 parts of composite silicon dioxide aerogel, 1 to 10 parts of softening agent, 7 to 20 parts of flame retardant, 0.5 to 5 parts of vulcanizing agent, 0.3 to 4 parts of accelerant and 0.1 to 3 parts of anti-aging agent. The compatibility between the phenolic resin and the EPDM raw rubber is improved, and the components such as the composite silicon dioxide aerogel, the flame retardant and the scorch retarder are cooperated, so that the scorch time of the EPDM material is long, the processing fluidity is good, the thermal aging resistance is excellent, and the overall mechanical property is relatively high in retention degree before and after aging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of rubber material production, and in particular to an EPDM material with good scorch resistance and fluidity and a preparation method thereof. Background Art

[0002] In the processing of rubber products, such as mixing, molding and vulcanization, it takes a certain amount of time to complete the operation. If the scorch resistance of ethylene propylene diene monomer rubber (EPDM) is poor, premature vulcanization during the processing will cause the fluidity of the rubber to deteriorate, and the subsequent molding operation cannot be carried out smoothly. This will lead to production interruptions and affect the production efficiency of rubber products. On the other hand, scorch will increase the viscosity of EPDM rubber, deteriorate the processing performance, and increase the difficulty of EPDM processing and molding. Once the mixed rubber is burned, the rubber will be partially cooked, affecting the fluidity of the later molding process and the appearance performance of the finished product, and even causing a large amount of EPDM rubber materials to be unable to be used normally. At the same time, the scorch process will release some harmful gases, causing pollution to the environment and human body. Therefore, improving the scorch resistance of EPDM materials and reducing the occurrence of scorch are of great significance for the production and processing of EPDM materials and products. Summary of the invention

[0003] The purpose of the present invention is to solve the above-mentioned deficiencies in the prior art and to provide an EPDM material with good scorch resistance and fluidity and a preparation method thereof.

[0004] The object of the present invention is achieved by the following technical scheme: an EPDM material with good anti-scorching fluidity, comprising the following raw materials in parts by weight: 50-80 parts of EPDM raw rubber, 5-8 parts of phenolic resin, 0.2-3 parts of scorch retarder, 4-7 parts of zinc methacrylate, 0.5-3 parts of stearic acid, 5-15 parts of composite silica aerogel, 1-10 parts of softener, 7-20 parts of flame retardant, 0.5-5 parts of vulcanizer, 0.3-4 parts of accelerator and 0.1-3 parts of antioxidant.

[0005] Furthermore, the phenolic resin is a modified phenolic resin, and its preparation method comprises the following steps:

[0006] S1. Add sodium hydroxide aqueous solution to phenol to fully dissolve, then add formalin and stir evenly, and condense and reflux at 60-65°C for 1-1.5h;

[0007] S2, then adding acetic acid aqueous solution to adjust the pH of the system to neutral, and then transferring to 75-80° C. to perform reduced pressure distillation to obtain a viscous liquid;

[0008] S3, then add phenylboric acid to the viscous liquid obtained in step S2, raise the temperature to 88-92°C, condense and reflux for 1-1.5h to obtain a yellow low-viscosity liquid, and then switch to reduced pressure distillation to dehydrate to obtain a yellow viscous liquid;

[0009] S4, adding the silicone resin ethanol solution and aminopropyltrimethoxysilane to the yellow viscous liquid obtained in step S3 and mixing them evenly, then adding ethanol and mixing them thoroughly, and heating and curing to obtain the modified phenolic resin.

[0010] Furthermore, in step S4, the mass ratio of the yellow viscous liquid to the silicone resin is 1:1, the aminopropyltrimethoxysilane is 6-8wt% of the yellow viscous liquid, and the curing temperature is 150-160°C.

[0011] In the present invention, the modified phenolic resin prepared by the above method can be uniformly dispersed in the EPDM material, limiting the excessive movement and mutual contact of the EPDM molecular chains during the processing, thereby helping to delay the occurrence of scorch. Furthermore, since the modified phenolic resin itself has good thermal stability, it can absorb part of the heat when uniformly dispersed in the EPDM system, reduce the local temperature of the rubber system, and thus play a role in extending the scorch time.

[0012] Furthermore, the anti-scorching agent is at least one of N-cyclohexylthiophthalimide, thiodimethylimide derivative GE1907, and N-phenyl-N-trichloromethylsulfonyl-phenylsulfonylanilide.

[0013] Furthermore, the preparation method of the composite silica aerogel comprises the following steps:

[0014] A1. Take a strong acid styrene cation exchange resin in a volume ratio of 1:2 and add it to a 5% dilute hydrochloric acid solution and stir for 2-3 hours, then filter and wash to obtain an activated strong acid styrene cation exchange resin.

[0015] A2, adding 25% industrial water glass dropwise to the activated strong acid styrene cation exchange resin obtained in step A1 at a volume ratio of 1:1-1.2, and stirring for 0.5-1h to obtain silica sol;

[0016] A3, adding silica sol dropwise to a zinc salt solution with a concentration of 0.3-0.4 mol / L at a volume ratio of 2-3:1, adding hexadecyltrimethylammonium bromide thereto and stirring the reaction for 1-2 hours, then adding potassium hydroxide solution to adjust the pH of the reaction system to 9-10, then transferring to a reaction vessel, controlling the reaction temperature to 160-180°C, the reaction time to 12-16 hours, cooling naturally after completion, centrifuging, washing, and drying to obtain a wet gel product;

[0017] A4. Pre-freeze the wet gel product obtained in step A3 at -80°C for 2-3 hours, and then freeze-dry it in a vacuum freeze dryer to obtain the composite silica aerogel.

[0018] Furthermore, in step A4, the freeze-drying temperature is -70 to -75°C and the time is 36 to 48 hours.

[0019] The composite silica aerogel prepared by the above method has the characteristics of multiple pores and high specific surface area, and by loading nano zinc dioxide on the silica aerogel, the silica aerogel has a strong interaction with the EPDM material, playing an effective reinforcing role, and the nano zinc oxide can not only promote the formation of an effective cross-linked network between the EPDM materials, but also utilize its good thermal conductivity and chemical stability to cooperate with the silica aerogel to improve the aging resistance and heat resistance of the EPDM material.

[0020] Furthermore, the softener is at least one of paraffin oil, aromatic oil, cycloparaffin oil, and liquid isoprene.

[0021] Furthermore, the flame retardant is at least one of aluminum hydroxide, expanded graphite, organic montmorillonite, and zinc borate. As a preferred embodiment of the present invention, the flame retardant is compounded by expanded graphite, aluminum hydroxide, and organic montmorillonite in a mass ratio of 5:1.5:1, wherein the aluminum hydroxide is aluminum hydroxide treated with KH-550 and has a particle size of 2000-2500 mesh.

[0022] Furthermore, the vulcanizing agent is at least one of dicumyl peroxide, di-tert-butyl diisopropylbenzene peroxide, and benzoyl peroxide, and the vulcanizing agent is preferably a compound of di-tert-butyl diisopropylbenzene peroxide and benzoyl peroxide in a mass ratio of 4-5:1.

[0023] Furthermore, the accelerator is at least one of sulfonamide accelerators, tetrabenzylthiuram disulfide, zinc dibutyldithiocarbamate or triallyl cyanurate.

[0024] Furthermore, the antioxidant is at least one of antioxidant BLE, antioxidant 1010, antioxidant RD, antioxidant 4010NA, and antioxidant 2246.

[0025] The present invention also provides a method for preparing the EPDM material with good scorch resistance and fluidity, comprising the following steps:

[0026] (1) Add EPDM raw rubber, phenolic resin, zinc methacrylate, stearic acid, composite silica aerogel, softener and flame retardant into an internal mixer for mixing in multiple times, with the initial internal mixing temperature of 50-60° C., the debonding time of 6-8 min, and the debonding temperature of 130-140° C.;

[0027] (2) Transfer to an open mixing mill for mixing. After the rubber material is wrapped around a roller, add a vulcanizer, an accelerator, an anti-scorch agent and an anti-aging agent. After the material is finished, cut the rubber three times on the left and right sides to make it evenly mixed. Thin it 6-10 times, exhaust the air, and put it on the sheet to obtain an EPDM material.

[0028] The beneficial effects of the present invention are as follows: the present invention discloses an EPDM material with good scorch resistance and fluidity, which uses EPDM raw rubber as a matrix raw material, and can effectively delay scorch and improve processing performance while enhancing the mechanical properties of EPDM by introducing modified phenolic resin, and also improves the compatibility of the material matrix, so that components such as composite silica aerogel and flame retardant can be evenly dispersed in the matrix, wherein the composite silica aerogel works together with the flame retardant, scorch inhibitor and zinc methacrylate while effectively reinforcing, thereby significantly improving the heat aging resistance and scorch resistance of the EPDM material. DETAILED DESCRIPTION

[0029] In order to facilitate the understanding of those skilled in the art, the present invention is further described below in conjunction with embodiments, and the contents mentioned in the implementation modes are not intended to limit the present invention.

[0030] The EPDM raw rubber used in the following embodiments and comparative examples of the present invention is Keltan 8550, with a Mooney viscosity of 80 at 125° C., an ethylene unit mass fraction of 55%, and the third monomer is ethylidene norbornene (ENB), with a mass fraction of 5.5%.

[0031] Example 1

[0032] The present embodiment provides an EPDM material with good scorch resistance and fluidity, comprising the following raw materials in parts by weight: 60 parts of EPDM raw rubber, 6 parts of phenolic resin, 1 part of scorch retarder, 5 parts of zinc methacrylate, 1 part of stearic acid, 6 parts of composite silica aerogel, 5 parts of softener, 12 parts of flame retardant, 3 parts of vulcanizer, 1.5 parts of accelerator, and 0.8 parts of antioxidant.

[0033] Furthermore, the phenolic resin is a modified phenolic resin, and its preparation method comprises the following steps:

[0034] S1. Add 4 mol / L sodium hydroxide aqueous solution to 5 g phenol to fully dissolve, then add 7.5 mL 37 wt % formalin and stir evenly, and condense and reflux at 60 ° C for 1.5 h;

[0035] S2, adding 36 wt % acetic acid aqueous solution to adjust the pH of the system to neutral, and then transferring to 75° C. to obtain a viscous liquid by vacuum distillation;

[0036] S3, then add 0.5g of phenylboric acid to the viscous liquid obtained in step S2, raise the temperature to 90°C, condense and reflux for 1h to obtain a yellow low-viscosity liquid, and then switch to reduced pressure distillation to dehydrate to obtain a yellow viscous liquid;

[0037] S4, adding 70 wt % silicone resin ethanol solution and aminopropyltrimethoxysilane to the yellow viscous liquid obtained in step S3 and mixing them evenly, then adding ethanol and mixing them thoroughly, and heating and curing to obtain the modified phenolic resin.

[0038] Furthermore, in step S4, the mass ratio of the yellow viscous liquid to the silicone resin is 1:1, the aminopropyltrimethoxysilane is 7wt% of the yellow viscous liquid, and the curing temperature is 150°C.

[0039] Furthermore, the anti-scorching agent is compounded by N-cyclohexylthiophthalimide and thiodimethylimide derivative GE1907 in a mass ratio of 2:1.

[0040] Furthermore, the preparation method of the composite silica aerogel comprises the following steps:

[0041] A1. Take a strong acid styrene cation exchange resin in a volume ratio of 1:2 and add it to a 5% dilute hydrochloric acid solution and stir for 2 hours, then filter and wash to obtain an activated strong acid styrene cation exchange resin.

[0042] A2, adding 25% industrial water glass dropwise to the activated strong acid styrene cation exchange resin obtained in step A1 at a volume ratio of 1:1.1, and stirring for 0.5 h to obtain silica sol;

[0043] A3, adding silica sol dropwise to a zinc salt solution with a concentration of 0.35 mol / L at a volume ratio of 2.5:1, adding hexadecyltrimethylammonium bromide thereto and stirring the reaction for 1 hour, then adding potassium hydroxide solution to adjust the pH of the reaction system to 9, then transferring to a reaction vessel, controlling the reaction temperature to 160°C, the reaction time to 16 hours, cooling naturally after the reaction, centrifuging, washing, and drying to obtain a wet gel product;

[0044] A4. Pre-freeze the wet gel product obtained in step A3 at -80°C for 2 hours, and then freeze-dry it in a vacuum freeze dryer to obtain the composite silica aerogel.

[0045] Furthermore, in step A4, the freeze-drying temperature is -70°C and the time is 48 hours.

[0046] Furthermore, the softener is cyclohexane oil.

[0047] Furthermore, the flame retardant is compounded by expanded graphite, aluminum hydroxide and organic montmorillonite in a mass ratio of 5:1.5:1, wherein the aluminum hydroxide is aluminum hydroxide treated with KH-550 and has a particle size of 2000 meshes.

[0048] Furthermore, the vulcanizing agent is compounded by di-tert-butyl peroxide diisopropylbenzene and benzoyl peroxide in a mass ratio of 4:1.

[0049] Furthermore, the accelerator is N,N-dicyclohexyl-2-benzothiazole sulfenamide.

[0050] Furthermore, the antioxidant is antioxidant RD.

[0051] The present invention also provides a method for preparing the EPDM material with good scorch resistance and fluidity, comprising the following steps:

[0052] (1) Add EPDM raw rubber, phenolic resin, zinc methacrylate, stearic acid, composite silica aerogel, softener and flame retardant into an internal mixer in multiple batches for mixing, with the initial internal mixing temperature being 50° C., the debonding time being 7 min, and the debonding temperature being 135° C.;

[0053] (2) Transfer to an open mixing mill for mixing. After the rubber material is wrapped around a roller, add a vulcanizer, an accelerator, an anti-scorch agent and an anti-aging agent. After the material is finished, cut the rubber three times on the left and right sides to make it evenly mixed. Thin it 10 times, exhaust the air, and take it off the sheet to obtain an EPDM material.

[0054] Example 2

[0055] The present embodiment provides an EPDM material with good anti-scorching and fluidity, comprising the following raw materials in parts by weight: 70 parts of EPDM raw rubber, 7 parts of phenolic resin, 2 parts of scorch retarder, 5 parts of zinc methacrylate, 1.5 parts of stearic acid, 10 parts of composite silica aerogel, 4 parts of softener, 12 parts of flame retardant, 3 parts of vulcanizer, 2 parts of accelerator, and 1.5 parts of antioxidant.

[0056] Furthermore, the phenolic resin is a modified phenolic resin, and its preparation method comprises the following steps:

[0057] S1. Add 4 mol / L sodium hydroxide aqueous solution to 5 g phenol to fully dissolve, then add 7.5 mL 37 wt % formalin and stir evenly, and condense and reflux at 65 ° C for 1 h;

[0058] S2, adding 36 wt % acetic acid aqueous solution to adjust the pH of the system to neutral, and then transferring to 78° C. to perform reduced pressure distillation to obtain a viscous liquid;

[0059] S3, then add 0.5g of phenylboric acid to the viscous liquid obtained in step S2, raise the temperature to 90°C, condense and reflux for 1h to obtain a yellow low-viscosity liquid, and then switch to reduced pressure distillation to dehydrate to obtain a yellow viscous liquid;

[0060] S4, adding 70 wt % silicone resin ethanol solution and aminopropyltrimethoxysilane to the yellow viscous liquid obtained in step S3 and mixing them evenly, then adding ethanol and mixing them thoroughly, and heating and curing to obtain the modified phenolic resin.

[0061] Furthermore, in step S4, the mass ratio of the yellow viscous liquid to the silicone resin is 1:1, the aminopropyltrimethoxysilane is 7wt% of the yellow viscous liquid, and the curing temperature is 155°C.

[0062] Furthermore, the anti-scorching agent is prepared by compounding N-cyclohexylthiophthalimide and N-phenyl-N-trichloromethylsulfonyl-phenylsulfonylanilide in a mass ratio of 2:1.

[0063] Furthermore, the preparation method of the composite silica aerogel comprises the following steps:

[0064] A1. Take a strong acid styrene cation exchange resin in a volume ratio of 1:2 and add it to a 5% dilute hydrochloric acid solution and stir for 2-3 hours, then filter and wash to obtain an activated strong acid styrene cation exchange resin.

[0065] A2, adding 25% industrial water glass dropwise to the activated strong acid styrene cation exchange resin obtained in step A1 at a volume ratio of 1:1.1, and stirring for 1 hour to obtain silica sol;

[0066] A3, adding silica sol dropwise to a zinc salt solution with a concentration of 0.35 mol / L at a volume ratio of 2.5:1, adding hexadecyltrimethylammonium bromide thereto and stirring the reaction for 1.5 hours, then adding potassium hydroxide solution to adjust the pH of the reaction system to 9, then transferring to a reaction vessel, controlling the reaction temperature to 170°C, the reaction time to 12 hours, cooling naturally after the reaction, centrifuging, washing, and drying to obtain a wet gel product;

[0067] A4. Pre-freeze the wet gel product obtained in step A3 at -80°C for 2.5 hours, and then freeze-dry it in a vacuum freeze dryer to obtain the composite silica aerogel.

[0068] Furthermore, in step A4, the freeze-drying temperature is -75°C and the time is 48 hours.

[0069] Furthermore, the softener is paraffin oil.

[0070] Furthermore, the flame retardant is compounded by expanded graphite, aluminum hydroxide and organic montmorillonite in a mass ratio of 5:1.5:1, wherein the aluminum hydroxide is aluminum hydroxide treated with KH-550 and has a particle size of 2500 meshes.

[0071] Furthermore, the vulcanizing agent is compounded by di-tert-butyl peroxide diisopropylbenzene and benzoyl peroxide in a mass ratio of 4:1.

[0072] Furthermore, the accelerator is compounded by tetrabenzylthiuram disulfide and zinc dibutyldithiocarbamate in a mass ratio of 1:2.

[0073] Furthermore, the antioxidant is antioxidant 2246.

[0074] The present invention also provides a method for preparing the EPDM material with good scorch resistance and fluidity, comprising the following steps:

[0075] (1) Add EPDM raw rubber, phenolic resin, zinc methacrylate, stearic acid, composite silica aerogel, softener and flame retardant into an internal mixer in multiple batches for mixing, with the initial internal mixing temperature being 55° C., the debonding time being 7 min, and the debonding temperature being 140° C.;

[0076] (2) Transfer to an open mixing mill for mixing. After the rubber material is wrapped around a roller, add a vulcanizer, an accelerator, an anti-scorch agent and an anti-aging agent. After the material is finished, cut the rubber three times on the left and right sides to make it evenly mixed. Thin it 10 times, exhaust the air, and take it off the sheet to obtain an EPDM material.

[0077] Example 3

[0078] The present embodiment provides an EPDM material with good scorch resistance and fluidity, comprising the following raw materials in parts by weight: 80 parts of EPDM raw rubber, 7 parts of phenolic resin, 2.5 parts of scorch retarder, 6 parts of zinc methacrylate, 2.5 parts of stearic acid, 13 parts of composite silica aerogel, 8 parts of softener, 16 parts of flame retardant, 4 parts of vulcanizer, 3 parts of accelerator, and 2.5 parts of antioxidant.

[0079] Furthermore, the phenolic resin is a modified phenolic resin, and its preparation method comprises the following steps:

[0080] S1. Add 4 mol / L sodium hydroxide aqueous solution to 5 g phenol to fully dissolve, then add 7.5 mL 37 wt % formalin and stir evenly, and condense and reflux at 65 ° C for 1.5 h;

[0081] S2, adding 36 wt % acetic acid aqueous solution to adjust the pH of the system to neutral, and then transferring to 80° C. to obtain a viscous liquid under reduced pressure;

[0082] S3, then add 0.5g of phenylboric acid to the viscous liquid obtained in step S2, raise the temperature to 90°C, condense and reflux for 1h to obtain a yellow low-viscosity liquid, and then switch to reduced pressure distillation to dehydrate to obtain a yellow viscous liquid;

[0083] S4, adding 70 wt % silicone resin ethanol solution and aminopropyltrimethoxysilane to the yellow viscous liquid obtained in step S3 and mixing them evenly, then adding ethanol and mixing them thoroughly, and heating and curing to obtain the modified phenolic resin.

[0084] Furthermore, in step S4, the mass ratio of the yellow viscous liquid to the silicone resin is 1:1, the aminopropyltrimethoxysilane is 8wt% of the yellow viscous liquid, and the curing temperature is 160°C.

[0085] Furthermore, the anti-scorching agent is prepared by compounding N-cyclohexylthiophthalimide and N-phenyl-N-trichloromethylsulfonyl-phenylsulfonylanilide in a mass ratio of 2:1.

[0086] Furthermore, the preparation method of the composite silica aerogel comprises the following steps:

[0087] A1. Take a strong acid styrene cation exchange resin in a volume ratio of 1:2 and add it to a 5% dilute hydrochloric acid solution and stir for 3 hours, then filter and wash to obtain an activated strong acid styrene cation exchange resin.

[0088] A2, adding 25% industrial water glass dropwise to the activated strong acid styrene cation exchange resin obtained in step A1 at a volume ratio of 1:1.2, and stirring for 1 hour to obtain silica sol;

[0089] A3, adding silica sol dropwise to a zinc salt solution with a concentration of 0.4 mol / L at a volume ratio of 3:1, adding hexadecyltrimethylammonium bromide thereto and stirring the reaction for 2 hours, then adding potassium hydroxide solution to adjust the pH of the reaction system to 10, then transferring to a reaction vessel, controlling the reaction temperature to 180°C, the reaction time to 12 hours, cooling naturally after the reaction, centrifuging, washing, and drying to obtain a wet gel product;

[0090] A4. Pre-freeze the wet gel product obtained in step A3 at -80°C for 3 hours, and then freeze-dry it in a vacuum freeze dryer to obtain the composite silica aerogel.

[0091] Furthermore, in step A4, the freeze-drying temperature is -75°C and the time is 48 hours.

[0092] Furthermore, the softening agent is liquid isoprene.

[0093] Furthermore, the flame retardant is compounded by expanded graphite, aluminum hydroxide and organic montmorillonite in a mass ratio of 5:1.5:1, wherein the aluminum hydroxide is aluminum hydroxide treated with KH-550 and has a particle size of 2500 meshes.

[0094] Furthermore, the vulcanizing agent is compounded by di-tert-butyl peroxide diisopropylbenzene and benzoyl peroxide in a mass ratio of 5:1.

[0095] Furthermore, the accelerator is N-oxydiethylenethiocarbamoyl-N′-oxydiethylenesulfenamide.

[0096] Furthermore, the antioxidant is antioxidant 4010NA.

[0097] The present invention also provides a method for preparing the EPDM material with good scorch resistance and fluidity, comprising the following steps:

[0098] (1) Add EPDM raw rubber, phenolic resin, zinc methacrylate, stearic acid, composite silica aerogel, softener and flame retardant into an internal mixer in multiple batches for mixing, with the initial internal mixing temperature being 60° C., the debonding time being 8 min, and the debonding temperature being 140° C.;

[0099] (2) Transfer to an open mixing mill for mixing. After the rubber material is wrapped around a roller, add a vulcanizer, an accelerator, an anti-scorch agent and an anti-aging agent. After the material is finished, cut the rubber three times on the left and right sides to make it evenly mixed. Thin it 10 times, exhaust the air, and take it off the sheet to obtain an EPDM material.

[0100] Comparative Example 1

[0101] The difference between this comparative example and Example 2 is that the phenolic resin in Example 2 is not added to this comparative example.

[0102] Comparative Example 2

[0103] The difference between this comparative example and Example 2 is that the composite silica aerogel in Example 2 is not added in this comparative example.

[0104] Comparative Example 3

[0105] The difference between this comparative example and Example 2 is that the scorch retarder used in this comparative example is N-cyclohexylthiophthalimide, the flame retardant is expanded graphite, the vulcanizing agent is di-tert-butyl diisopropylbenzene peroxide, and the accelerator is tetrabenzylthiuram disulfide.

[0106] In the present invention, the test pieces (175°C×20min×10MPa) prepared in the above-mentioned Examples 1-3 and Comparative Examples 1-3 were tested for hardness, tensile strength, tear strength and elongation, wherein the hardness was tested according to the GB / T 531-2008 standard; the tensile strength and elongation at break were tested according to the GB / T 528-2009 standard, and the tensile strength and elongation at break of the test piece were tested again by hot air aging at 100°C*72h to examine its anti-aging performance. The Mooney scorch time was measured according to GB / T 1233-2008, and the test results are shown in the following table:

[0107]

[0108]

[0109] It can be seen from the data in the above table that the EPDM material prepared by the present invention has good overall mechanical properties, a hardness between 65-70HA, a tensile strength of 14.3-15.4MPa, an elongation at break of 516-528%, and after aging in hot air at 100°C*72h, the decrease in its tensile strength and elongation at break is small, indicating that the EPDM material has good heat resistance and stability. On the other hand, the Mooney scorch time of the EPDM materials of Examples 1-3 is more than 26.4min, indicating that the EPDM material has good anti-scorch performance and high processing safety.

[0110] The above specific embodiments are further explanations of the technical solutions and beneficial effects of the present invention, and are not limitations of the implementation methods. For those skilled in the art, any obvious replacements that do not depart from the concept of the present invention are within the protection scope of the present invention.

Claims

1. An EPDM material with good scorch resistance and fluidity, characterized by: The invention comprises the following raw materials in parts by weight: 50-80 parts of EPDM raw rubber, 5-8 parts of phenolic resin, 0.2-3 parts of scorch retarder, 4-7 parts of zinc methacrylate, 0.5-3 parts of stearic acid, 5-15 parts of composite silica aerogel, 1-10 parts of softener, 7-20 parts of flame retardant, 0.5-5 parts of vulcanizer, 0.3-4 parts of accelerator and 0.1-3 parts of antioxidant.

2. The EPDM material with good scorch resistance and fluidity according to claim 1, characterized in that: The phenolic resin is a modified phenolic resin, and its preparation method comprises the following steps: S1. Add sodium hydroxide aqueous solution to phenol to fully dissolve, then add formalin and stir evenly, and condense and reflux at 60-65°C for 1-1.5h; S2, then adding acetic acid aqueous solution to adjust the pH of the system to neutral, and then transferring to 75-80° C. to perform reduced pressure distillation to obtain a viscous liquid; S3, then add phenylboric acid to the viscous liquid obtained in step S2, raise the temperature to 88-92°C, condense and reflux for 1-1.5h to obtain a yellow low-viscosity liquid, and then switch to reduced pressure distillation to dehydrate to obtain a yellow viscous liquid; S4, adding the silicone resin ethanol solution and aminopropyltrimethoxysilane to the yellow viscous liquid obtained in step S3 and mixing them evenly, then adding ethanol and mixing them thoroughly, and heating and curing to obtain the modified phenolic resin.

3. The EPDM material with good scorch resistance and fluidity according to claim 1, characterized in that: The anti-scorch agent is at least one of N-cyclohexylthiophthalimide, thiodimethylimide derivative GE1907, and N-phenyl-N-trichloromethylsulfonyl-phenylsulfonylanilide.

4. The EPDM material with good scorch resistance and fluidity according to claim 1, characterized in that: The preparation method of the composite silica aerogel comprises the following steps: A1. Take a strong acid styrene cation exchange resin and add it to a dilute hydrochloric acid solution and stir for 2-3 hours, then filter and wash to obtain an activated strong acid styrene cation exchange resin. A2, adding industrial water glass dropwise to the activated strong acid styrene cation exchange resin obtained in step A1 and stirring for 0.5-1h to obtain silica sol; A3, adding silica sol dropwise to the zinc salt solution, adding hexadecyltrimethylammonium bromide thereto and stirring the reaction for 1-2 hours, then adding potassium hydroxide solution to adjust the pH of the reaction system to 9-10, then transferring to a reaction vessel, controlling the reaction temperature to 160-180°C, the reaction time to 12-16 hours, cooling naturally after completion, centrifuging, washing, and drying to obtain a wet gel product; A4. Pre-freeze the wet gel product obtained in step A3 for 2-3 hours, and then put it into a vacuum freeze dryer for freeze drying to obtain the composite silica aerogel.

5. The EPDM material with good scorch resistance and fluidity according to claim 1, characterized in that: The softener is at least one of paraffin oil, aromatic oil, cycloparaffin oil and liquid isoprene.

6. The EPDM material with good scorch resistance and fluidity according to claim 1, characterized in that: The flame retardant is at least one of aluminum hydroxide, expanded graphite, organic montmorillonite and zinc borate.

7. The EPDM material with good scorch resistance and fluidity according to claim 1, characterized in that: The vulcanizing agent is at least one of dicumyl peroxide, di-tert-butyl dicumyl peroxide, and benzoyl peroxide.

8. The EPDM material with good scorch resistance and fluidity according to claim 1, characterized in that: The accelerator is at least one of sulfenamide accelerators, tetrabenzylthiuram disulfide, zinc dibutyldithiocarbamate or triallyl cyanurate.

9. The EPDM material with good scorch resistance and fluidity according to claim 1, characterized in that: The antioxidant is at least one of antioxidant BLE, antioxidant 1010, antioxidant RD, antioxidant 4010NA, and antioxidant 2246.

10. The EPDM material with good scorch resistance and fluidity according to any one of claims 1 to 9, characterized in that: The steps include: (1) Add EPDM raw rubber, phenolic resin, zinc methacrylate, stearic acid, composite silica aerogel, softener and flame retardant into an internal mixer for mixing in multiple times, with the initial internal mixing temperature of 50-60° C., the debonding time of 6-8 min, and the debonding temperature of 130-140° C.; (2) Transfer to an open mixing mill for mixing. After the rubber material is wrapped around a roller, add a vulcanizer, an accelerator, an anti-scorch agent and an anti-aging agent. After the material is finished, cut the rubber three times on the left and right sides to make it evenly mixed. Thin it 6-10 times, exhaust the air, and put it on the sheet to obtain an EPDM material.

Citation Information

Patent Citations

  • Composite aerogel and fireproof heat-insulation felt and preparation method thereof

    CN107376794A

  • Sound-insulation heat-preservation rubber product and preparation method thereof

    CN110372966A

  • EPDM (Ethylene-Propylene-Diene Monomer) rubber material for sealing sheath and preparation method thereof

    CN116444902A

  • Heat-aging-resistant ethylene propylene diene monomer composition and preparation method thereof

    CN117264334A

  • Method for preparing high-strength stemming from waste refractory material

    CN118108515A